Present-day changes of mountain glaciers on the southern slope of the Dzhungarian Alatau range - A. L. Kokarev; I. N. Shesterova (Лëд и снег, 2015)
Glacierization of southern slope of the Dzhungarian (Zhetysu) Alatau range was estimated by means of data obtained by operational satellite Landsat 7 surveys on August 19 and September 2011 (sensors ETM+) with the use of digital relief models (ASTER GDEM). Analysis of these materials by means of computer programs ENVI, ERDAS Imagine, MapInfo, and ArcGIS made it possible to obtain a spatial information of glacier systems of the territory under investigation and to define morphological characteristics of glaciers, present-day moraine complexes, glacier lakes as well as other elements of glacial monitoring at the survey moments. To estimate changes of the glacierization the data from previous Inventories of this glacier system as of 1956 and 1972 (P.A. Cherkasov), 1990 and 2000 (authors of this article) were used. 30 glaciers being now located on the Chine territory but included into the Inventories of 1956 and 1972 (because the boundaries were changed after 1990) were included into new Inventory.As of 2011, 500 glaciers with total area of their open parts 120.12 km2 were registered in Southern Dzhungaria. 124 glaciers (57% of total number) cover area less 0.1 km2 each, and their total area is equal to 9.01 km2 (8% of total area of the glacierization).Total area of the moraines reached 105.6 km2. Volume of open ice calculated by formulas was estimated 4.6 km3. According to calculations, the firn line altitude of the glaciers on the southern slope was equal to 3685 m. As compared to 1956 (3645 m) this line lifted by 40 m. 190 glacier lakes with total area 6.0 km2 were found on this territory, among them 19 lakes were classified as especially dangerous for outbursting (their total area – 2.5 km2).For the last 55 years the glacierization area in the Southern Dzhungaria was reduced by 47.4% or, on the average, by 0.86% in every year. It should be noted that for the several last years, the rate of degradation decreased almost twice as compared to earlier years. The tendencies revealed were used to predict future changes of the glaciarization area on southern slope of the Dzhungarian Alatau range by the end of current century. According to this prediction, if the climatic conditions will not change, glaciers of this region will possibly be existing, however, their area will amount not more than 24% of the glacierization area of 1956.